Issues in Restructuring of Sovereign Domestic Debt. (Policy Papers; Policy Paper ;, 2021)
As emerging and developing economies accumulate more domestic sovereign debt, it is likely to play a larger role in the resolution of future sovereign debt crises. This paper analyzes when and how to restructure sovereign domestic debt in unsustainable debt cases while minimizing economic and financial disruptions. Key to determining whether or not domestic debt should be part of a sovereign restructuring is weighing the benefits of the lower debt burden against the fiscal and broader economic costs of achieving that debt relief. The fiscal costs may have to be incurred in the context of restructuring because of the need to maintain financial stability, to ensure the functioning of the central bank, or to replenish pension savings. A sovereign domestic debt restructuring should be designed to anticipate, minimize, and manage its impact on the domestic economy and financial system. Casting the net wide across claims can help boost participation in the restructuring by lowering the relief sought from each creditor group. A strategy that engages creditors constructively, and as transparently as possible, that relies on market-based incentives, and that presents the exchange as part of a consistent macroeconomic plan typically works best.